Corvis ST biomarkers in healthy and keratoconus eyes: clinical and numerical evaluation - Redaelli, Elena; Calvo, Begoña; Rodríguez Matas, José Félix; Luraghi, Giulia (Jornada de Jóvenes Investigadores del I3A, 2022)
Non-Contact Tonometry (NCT) is a diagnostic tool intended to characterize corneal biomechanics in vivo. In order to analyze the response of the corneal tissue behavior, a numerical model could be of great help. This work aims to validate an in-silico NCT by comparing the clinical biomarkers of four patients to the numerical results of the same patient-specific simulations.